Case Study of Nursing Care with Pressure Bandage Technique on Nursing Problems of Post PCI Bleeding Risk in the Heart Room of General Ahmad Yani Hospital Metro City - Triwibowo, Wahyu; Sugiarto, Sugiarto; Wardoyo, Eko (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2025)
Background & Objective: Acute coronary syndrome (SCA) is a set of symptoms that occur due to the accumulation of atherosclerotic plaque in the walls of blood vessels, which is part of Coronary Heart Disease (CHD). The purpose of this study was to determine the description of nursing care with pressure dressing techniques in patients with nursing problems of Post PCI bleeding risk. Method: This type of research is descriptive research using the case study method. The action taken is the application of the pressure dressing technique using a mechanical pressing device on the puncture area where the catheter is inserted after the PCI procedure. The monitoring process was carried out for 2 x 24 hours after the application of the technique to assess the effectiveness of the intervention and monitor signs of bleeding. Result: After 2 x 24 hours of treatment, there were no signs of bleeding, the acral was warm and pain at the puncture area was reduced. Conclusion: Answering the research objectives. Should The risk of bleeding can be well managed through treatment with the pressure dressing technique.